Hadiths and Athars Regarding Eid and Friday Prayers: Collection and Critical Study - Jamshir, D. Fwad Saif Allah Jamshir (Sulaimani Journal for Humanities, 2025)
This research deals with an old controversial issue that occurred since the time of the honorable Companions, may God be pleased with them, and it contains several hadiths and traces of the Prophet, may God’s prayers and peace be upon him, and some of the honorable Companions, may God be pleased with them. Hadith according to the rules and rules of modern scholars.
Keywords: Hadith authentication; Controversial hadith; Companions disputes